2012
DOI: 10.1007/s10508-012-0015-7
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Fa’afafine Relatives Among Samoan Gynephilic Men and Fa’afafine

Abstract: Androphilia refers to sexual attraction to adult males whereas gynephilia refers to sexual attraction to adult females. In Western populations, androphilia in males is familial, but the precise nature of this phenomenon is unclear. Some studies show that androphilic males have preponderances of androphilic male relatives in the maternal, but not paternal, line. In contrast, other studies show that male androphilia clusters in both the maternal and paternal lines. Low fertility populations are susceptible to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…In terms of biodemographic correlates, when compared to gynephilic males, both sex-gender congruent and transgendered male androphiles tend to be later born among their siblings (e.g., Blanchard, 2004;Vander-Laan & Vasey, 2011;, have greater numbers of older biological brothers (''fraternal birth order effect 1 ,'' e.g., Bogaert & Skorska, 2011;, exhibit larger family sizes (e.g., Blanchard & Lippa, 2007;Camperio-Ciani, Corna & Capiluppi, 2004;Iemmola & Camperio Ciani, 2009;King et al 2005;Schwartz, Kim, Kolundzija, Rieger & Sanders, 2010;VanderLaan, Forrester, Petterson & Vasey, 2012;, cluster within families (e.g., Schwartz et al, 2010;VanderLaan, Forrester, Petterson & Vasey, 2013;VanderLaan, Vokey & Vasey, 2013), occur at similar prevalence rates across cultures (e.g., Smith, Rissel, Richters, Grulich & de Visser, 2003;VanderLaan, Forrester, et al, 2013;Whitam, 1983), and exhibit little or no reproductive output (e.g., King et al, 2005;Schwartz et al, 2010;Vasey, Parker & VanderLaan, 2014). In addition, the odds ratios associated with the fraternal birth order effect in various populations of sex-gender congruent and transgendered male androphiles are remarkably consistent, suggesting that the manner in which older brothers influence the development of male androphilia is constant across culturally diverse populations (e.g., Cantor, Blanchard, Paterson & Bogaert, 2002;.…”
Section: Some Correlates Of Male Androphilia Reoccur Consistently Acrmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of biodemographic correlates, when compared to gynephilic males, both sex-gender congruent and transgendered male androphiles tend to be later born among their siblings (e.g., Blanchard, 2004;Vander-Laan & Vasey, 2011;, have greater numbers of older biological brothers (''fraternal birth order effect 1 ,'' e.g., Bogaert & Skorska, 2011;, exhibit larger family sizes (e.g., Blanchard & Lippa, 2007;Camperio-Ciani, Corna & Capiluppi, 2004;Iemmola & Camperio Ciani, 2009;King et al 2005;Schwartz, Kim, Kolundzija, Rieger & Sanders, 2010;VanderLaan, Forrester, Petterson & Vasey, 2012;, cluster within families (e.g., Schwartz et al, 2010;VanderLaan, Forrester, Petterson & Vasey, 2013;VanderLaan, Vokey & Vasey, 2013), occur at similar prevalence rates across cultures (e.g., Smith, Rissel, Richters, Grulich & de Visser, 2003;VanderLaan, Forrester, et al, 2013;Whitam, 1983), and exhibit little or no reproductive output (e.g., King et al, 2005;Schwartz et al, 2010;Vasey, Parker & VanderLaan, 2014). In addition, the odds ratios associated with the fraternal birth order effect in various populations of sex-gender congruent and transgendered male androphiles are remarkably consistent, suggesting that the manner in which older brothers influence the development of male androphilia is constant across culturally diverse populations (e.g., Cantor, Blanchard, Paterson & Bogaert, 2002;.…”
Section: Some Correlates Of Male Androphilia Reoccur Consistently Acrmentioning
confidence: 99%
“…Perhaps more compelling is research that suggests that male androphilia occurs in the majority of cultures for which data are available (e.g., Murray, 2000) and its population prevalence rate appears to be similar (~1.5-5%) across a variety of different cultures (e.g., Smith et al, 2003;VanderLaan, Forrester, et al, 2013;Whitam, 1983). Thus, male androphilia appears to be a predictably and reliably reoccurring phenomenon in most human cultures.…”
Section: The Existence Of Male Androphilia Is An Evolutionary Paradoxmentioning
confidence: 99%
“…A well-established biomarker of sexual orientation is familiality of male same-sex sexual orientation. Same-sex sexual orientation clusters in families (21)(22)(23)(24)(25)(26)(27)(28), twin studies show greater sexual orientation concordance among monozygotic than dizygotic twins (29)(30)(31)(32)(33)(34), and molecular genetic studies have identified candidate genes associated with sexual orientation (35)(36)(37). As such, genetic mechanisms appear to at least partially influence male same-sex sexual orientation.…”
mentioning
confidence: 99%
“…As such, genetic mechanisms appear to at least partially influence male same-sex sexual orientation. The heritability of male sexual orientation is estimated at ∼0.32 (15), and the associated genetic factors appear to be inherited from both the maternal and paternal lines given that gay men, compared with heterosexual men, have more gay male family members in both their maternal (22)(23)(24)(25)27) and paternal lines (21,25,26,28). Consistent with this familiality research, male sexual orientation has been associated with genes on the X chromosome and autosomal chromosomes (23,38), with the largest studies finding associations with Xq28 (23,36,38), the sonic hedgehog gene on chromosome 7 (35,37), and the pericentromeric region of chromosome 8 (35)(36)(37).…”
mentioning
confidence: 99%
“…Thus, from an evolutionary standpoint, the frequency of MHP is expected to decrease. However, MHP has been described at least since antiquity (Crompton, 2003), and it is relatively common in several societies: between 3 and 12 % in South and East Asia (Cáceres, Konda, Pecheny, Chatterjee, & Lyerda, 2006), 2 and 6% in Western countries (review in Table 4.3 of Berman, 2003), and between 1.4-4.7% in Samoa (VanderLaan, Forrester, Petterson, & Vasey, 2013).…”
Section: Introductionmentioning
confidence: 99%